2021
DOI: 10.1113/ep089244
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary surfactant‐associated protein B regulates prostaglandin‐endoperoxide synthase‐2 and inflammation in chronic obstructive pulmonary disease

Abstract: Pulmonary surfactant-associated protein B (SFTPB) is a critical protein for lung homeostasis, and polymorphism of its gene is associated with chronic obstructive pulmonary disease (COPD). However, few studies have so far confirmed the functional involvement of SFTPB in COPD. Serum SFTPB and inflammatory cytokine levels were measured in 54 patients with acute exacerbation of COPD and 29 healthy controls. A549 cells were induced using 10% cigarette smoke extract (CSE) and treated with dexamethasone to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
(34 reference statements)
1
4
0
Order By: Relevance
“…In A-549 cells, an epithelial cell line derived from human lung carcinoma, which has been widely used as an in vitro model of human alveolar type II epithelial cells [169], the mRNA expression of SP-B was increased after treatment with CS in a concentrationdependent manner, in agreement with another study where an increase in the mRNA expression of all four proteins was observed [170]. Differently, the mRNA and protein levels of SP-B were significantly decreased in the CS group compared with the control group in another study [168], where dexamethasone reduced the effect of CS. Finally, another study found a reduction in SP-C expression in human alveolar epithelial cells after exposure to CS and correlated this effect with apoptosis [171].…”
Section: Cigarette Smoke Effect's On Composition and Abundance Of Sur...supporting
confidence: 83%
See 2 more Smart Citations
“…In A-549 cells, an epithelial cell line derived from human lung carcinoma, which has been widely used as an in vitro model of human alveolar type II epithelial cells [169], the mRNA expression of SP-B was increased after treatment with CS in a concentrationdependent manner, in agreement with another study where an increase in the mRNA expression of all four proteins was observed [170]. Differently, the mRNA and protein levels of SP-B were significantly decreased in the CS group compared with the control group in another study [168], where dexamethasone reduced the effect of CS. Finally, another study found a reduction in SP-C expression in human alveolar epithelial cells after exposure to CS and correlated this effect with apoptosis [171].…”
Section: Cigarette Smoke Effect's On Composition and Abundance Of Sur...supporting
confidence: 83%
“…Many animal studies have shown a protective effect of SP-D against oxidative stress, inflammation, autophagy and apoptosis induced by CS. This has been demonstrated by administering recombinant SP-D [92,167], by studying the effects of smoking on SP-D-deficient mice [92,167] or by transfecting SP-D plasmid DNA into A-549 cells [168]. According to these studies, increased SP-D levels after exposure to CS would therefore be a positive and protective response against smoking-induced damage.…”
Section: Cigarette Smoke Effect's On Composition and Abundance Of Sur...mentioning
confidence: 99%
See 1 more Smart Citation
“…Pulmonary diseases are among the most prevalent diseases worldwide, costing the lives of millions of people annually (Berman, 1991; Wang et al., 2016). In addition to the COVID‐19 pandemic, acute respiratory distress syndrome (ARDS), chronic obstructive pulmonary disease (COPD), and pulmonary arterial hypertension (PAH) cause significant pulmonary inflammation, inflicting irreversible damages and structural remodeling of the lung vasculature (Revercomb et al., 2020; Shah et al., 2021; Wang et al., 2021). PAH, for example, progressively and irreversibly alters the function of the pulmonary arteries, leading to right ventricular failure (Thompson & Lawrie, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the smaller size and larger active area of NiO NPs, they are more likely to lead to chronic pulmonary toxicity such as inflammatory damage, 3 fibrosis, 4 and even cancer 5 . Since inflammation was the basis of those diseases, 6 it was crucial to investigate NiO NPs‐induced pulmonary inflammatory damage and explore its molecular mechanisms.…”
Section: Introductionmentioning
confidence: 99%